Faktor-Faktor Yang Mempengaruhi Pelayanan Rawat Jalan Terhadap Penggunaan Rekam Medis Elektronik Di Rumah Sakit Umum Daerah Jatisampurna Bekasi - Muhammad Yaska Zharfan; Aswin Naldi Sahim; Zaharuddin Zaharuddin (Journal of Innovative and Creativity, 2025)
The purpose of this study is to determine what factors influence Outpatient Services on the Use of Electronic Medical Records at Jatisampurna Hospital. The method used is a quantitative research method with descriptive. The sampling technique with total sampling from employees of Jatisampurna Hospital, especially in the outpatient service section, is 40 respondents and the data analysis technique uses a multivariate analysis technique using the SEM-PLS application. Based on the multivariate analysis obtained, the hypothesis states that the use of EMR as a full moderator variable has a positive effect on outpatient services at Jatisampurna Hospital with a p-value of 0.047. HR also significantly influences outpatient services at Jatisampurna Hospital with a p-value of 0.017. Based on the perception of respondents at Jatisampurna Hospital, HR and the use of EMR are in the fairly good category. There are strong and significant implications of HR in improving outpatient services, as well as the use of EMR has a large and significant influence on outpatient services.